Iowa Birdline update, circa November 6, 1990, notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update circa November 6, 1990. Highlights of the notes include sightings of Tundra Swans, Snow Buntings, American Pipits, and a large number of waterfowl. Also of note was a first winter Lesser Black-backed Gull and a first winter Thayer's Gull. Epson - sheet feed/flatbed